The problem of truth and reality in Grisebach's thought - Rauche, Gerhard Albin (Department of Philosophy, 2016)
It is the purpose of this work to give a critical assessment of the lifelong struggle about the problem of truth and reality by a man who has nearly been forgotten, Eberhard GRISEBACH. Particularly in our time, however, a time ruled by "isms" and ideologies, that are passed off on gullible man as the truth, and that are hung before his eyes like veils preventing him from ever experiencing the "real" and coming face to face with it, Grisebach's teaching deserves the closest attention. This work is thus meant to pave the way for a further study of his philosophy, which may help man to adopt an attitude towards life which is more suited than the present one is to coping with the problem and the difficulties of the actual situation. The first lesson we learn when studying Grisebach is from his refusal to placate any doctrine, ideology, creed, etc. from the courage with which he puts in question man's sacrosanct truths, values and beliefs, and from the inexorable and uncompromising honesty and sober reflection exhibited by him in his search for the real. This undoubtedly great thinker, whose search for truth and the real was inspired by a genuine need, and in his later years by a great disstress, passed his formative years at a period, when a young generation in a young striving German Empire was hopefully and confidently searching for new values that corresponded with reality more than the idealistic past of an a priori metaphysics did. In all walks of life - the sciences, the arts, technology, and economy - unheard of possibilities seemed to present themselves.